Comparison of leakage rate after sleeve gastrectomy compared with gastric bypass - Salehnia, Hadi; Rashki Ghalehnoo, Sara; Dehghan, Abbas Ali (Novelty in Biomedicine, 2025)
Background: Gastric bypass and sleeve gastrectomy are two common types of bariatric surgery. Anastomotic leak is one of the common and fatal complications of these surgeries. The current study compared the leakage rate after sleeve gastrectomy and gastric bypass. Materials and Methods: This cross-sectional study was performed on patients who underwent bariatric surgery in Mortaz and Mojibinia Hospitals (Yazd-Iran) from 2016 to 2020. Age, sex, body mass index (BMI) before surgery, underlying disorders, surgery types (sleeve gastrectomy or gastric bypass), amount of weight loss, leakage, duration time between the end of the surgery, and occurrence of leakage were recorded. The patients were followed up for three months. The patients were observed for the presence of the leakage for two weeks after the operation. Results: A total of 713 patients were enrolled in the study; 427 underwent sleeve gastrectomy (59.89%), and 286 underwent gastric bypass surgery (40.11%). Of these patients, 43.3% were male. The age of performing the surgery significantly differed between the groups (P-value: 0.031). The gastric bypass group lost more weight than the sleeve gastrectomy group (P-value <0.001). The leakage rate was higher in patients operated on by gastric bypass than those operated on by sleeve gastrectomy (P-value = 0.032). Leakage time significantly differed between the groups (P-value = 0.043). Conclusion: Bypass gastrectomy has a higher leakage rate than sleeve gastrectomy, but it has a higher effect on weight loss.